Connecting Inner and Outer Peace: Buddhist Meditation Integrated with Peace Education - Brantmeier, Edward (In Factis Pax: Journal of Peace Education and Social Justice, 2023)
Connecting inner dimensions of peace education to outer dimensions of peace education is critical for transformative peace efforts aimed at curbing a cultural of violence and moving toward a culture of peace. The cultivation of inner peace can contribute to knowledge paradigms that are supportive of peace and can provide a foundation for social action toward supporting peaceful attitudes, dispositions, values, action-orientations, behaviors and social structures. Contemplative practices/meditations are essential to education for peace because inner and outer worlds are not mutually exclusive, rather they mirror and reinforce one another. Therefore, inner violence correlates with outer violence; inner peace correlates with outer peace. Aligning both nonviolent means with nonviolent ends is essential for building sustainable, renewable peace. The connection between being peace and doing peace needs to be more deeply fostered and explored in the field of peace education.